2022
DOI: 10.1038/s43016-022-00594-9
|View full text |Cite|
|
Sign up to set email alerts
|

Global dietary quality in 185 countries from 1990 to 2018 show wide differences by nation, age, education, and urbanicity

Abstract: Evidence on what people eat globally is limited in scope and rigour, especially as it relates to children and adolescents. This impairs target setting and investment in evidence-based actions to support healthy sustainable diets. Here we quantified global, regional and national dietary patterns among children and adults, by age group, sex, education and urbanicity, across 185 countries between 1990 and 2018, on the basis of data from the Global Dietary Database project. Our primary measure was the Alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 52 publications
1
28
1
5
Order By: Relevance
“…However, meta-analyses have revealed that increased sugar consumption is associated with increased energy intake in general, giving more credence to the notion that higher energy intake accounted for by all calories, rather than just sugar, is the cause of the obesity epidemic. International data show that carbohydrate consumption is declining but diet quality is still poor and calorie intake high [ 118 ]. Rather than just a case of too much sugar, could it be a case of too much food intake overall?…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-analyses have revealed that increased sugar consumption is associated with increased energy intake in general, giving more credence to the notion that higher energy intake accounted for by all calories, rather than just sugar, is the cause of the obesity epidemic. International data show that carbohydrate consumption is declining but diet quality is still poor and calorie intake high [ 118 ]. Rather than just a case of too much sugar, could it be a case of too much food intake overall?…”
Section: Introductionmentioning
confidence: 99%
“…The diet quality has increased from 1990 to 2018 in most parts of the world, but not in Sub-Saharan Africa (SSA). This clearly indicates the need of more focus on dietary issues in countries in SSA ( 1 ). Diet is an important modifiable risk factor associated with non-communicable diseases ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Al igual que en el resto del mundo, el patrón alimentario argentino se ha modificado en las últimas décadas, observándose una disminución del consumo de frutas y vegetales, harina de trigo, legumbres, carne vacuna y leche y un aumento del consumo de productos alimenticios ultraprocesados (UP) tales como masas comerciales, carnes procesadas, gaseosas, jugos y comidas listas para consumo 28 . Los UP se definen como aquellos que se obtienen por el agregado de ingredientes culinarios y de otras sustancias, como el jarabe de maíz de alta fructosa, los aceites hidrogenados, los emulsificantes o los edulcorantes no calóricos a alimentos como granos, legumbres, vegetales, frutas y carnes 29 Si bien los patrones alimentarios son dependientes de cada población [30][31][32][33] , en un estudio de revisión con metaanálisis 34 se halló que, la mayoría de las investigaciones realizadas sobre éstos a nivel mundial comparten la obtención de dos tipos de patrones principales con similares características de ingesta alimentaria, aunque en ocasiones son denominados de diferente forma por sus autores. Por un lado, se encuentra el patrón de alimentación saludable o "Prudente", que presenta cargas factoriales positivas en grupos de alimentos como frutas, vegetales, carnes blancas, lácteos reducidos en grasas, y granos enteros; y, por otro lado, el patrón de alimentación poco saludable u "Occidental", el cual tiende a presentar cargas factoriales positivas en grupos de alimentos como carnes rojas, carnes procesadas, granos refinados, vegetales feculentos, dulces y lácteos enteros.…”
Section: Etiología De La Obesidadunclassified
“…Los estudios epidemiológicos con enfoques más tradicionales utilizan los nutrientes o los grupos de alimentos como unidades de medida, aunque en la actualidad se apunta a la utilización de patrones alimentarios 27 . Por un lado, este enfoque permite clasificar y cuantificar la adherencia a dietas características de cada población (por ejemplo, la adherencia a la dieta mediterránea), aunque también conspira con la realización de estudios de metaanálisis para incrementar la validez científica de los hallazgos, ya que los patrones alimentarios son específicos de cada población [30][31][32][33] . Por esta razón, se propone que los estudios nutrigenéticos evalúen la ingesta utilizando ambos enfoques: midiendo la ingesta de nutrientes y alimentos (lo que permitirá las comparaciones) e incluyendo además el enfoque de patrones alimentarios, información que será útil para cada población en particular 103 .…”
Section: Componente Nutricional En Estudios Nutrigenéticos: Evaluació...unclassified
See 1 more Smart Citation